Determination of the optimum potential window for super- and pseudocapacitance electrodes via in-depth electrochemical impedance spectroscopy analysis. (15th December 2022) - Khayyam Nekouei, Rasoul; S. Mofarah, Sajjad; Maroufi, Samane; Tudela, Ignacio; Sahajwalla, Veena
Abstract: Electrochemical analysis of energy storage materials in aqueous electrolytes requires an accurate determination of a working potential window. Applying potentials outside this window causes detrimental reactions, reducing the electrode's durability. Therefore, there is a need for rapid and accurate determination of the most desired potential window in the assembly of energy storage materials. The present work reports a novel single equivalent circuit model based on electrochemical impedance spectroscopy (EIS), Nyquist plots, and Bode plots that is capable of predicting the optimal operating potential of both electric double-layer capacitors (EDLCs) and pseudocapacitors. The model was evaluated on four electrodes, two EDLCs made of activated carbon derived from coffee residue and waste textile, and two MnOx and Mn1−x−y (Cex Lay )O2−δ pseudocapacitors. A ratio of Capacitance of diffusion Capacitance of double layer was defined and calculated at different DC potential windows. Results indicated that the optimum potential window is obtained at a ratio below 3 % for supercapacitors. The larger potential windows resulted in a significant increase in the ratio as a result of the emergence of unfavourable Faradic reactions. To address this issue, a mathematical factor (i.e., χ 2 ) was defined and plotted vs. applied potential, verifying the accuracy of the optimum potential window for pseudocapacitors. Additionally, analysis of Bode plots indicated the presence of unfavourable Faradic reactions at voltages that exceeded the optimum potential window. Therefore, results of our proposed method have proven to be more reliable, rapid, sensitive, and accurate than those obtained using conventional cyclic voltammetry. Highlights: Presenting a novel method for rapid and efficient determination of an optimal working ΔV Expanding the method's applicability to super- and pseudocapacitance electrodes A detailed investigation of EIS (Nyquist and Bode plots) to simulate both super- and pseudocapacitors Producing the C diffusion C dl for determining an optimal ΔV for supercapacitors Producing a mathematical factor of χ 2 indicating an optimum ΔV for pseudocapacitors